Evaluation of F18 enterotoxigenic Escherichia coli intestinal attachment and early disease onset in nursery pigs - Due, Elizabeth M.; Miller, Kayla A.; Burrough, Eric R.; Helm, Emma T.; Gabler, Nicholas K. (Frontiers in Veterinary Science, 2025)
IntroductionEnterotoxigenic Escherichia coli (ETEC) is a major cause of post-weaning diarrhea and reduced performance in nursery pigs. While ETEC pathogenesis is well established, the early epithelial and functional responses to F18 ETEC infection remain poorly defined. This study investigated the effects of F18 ETEC on bacterial attachment, intestinal function, and early epithelial cell responses.MethodsTen days post-weaning, 24 individually housed pigs (n = 6/treatment) were orally inoculated with 5 ml of F18 ETEC at 107, 108, or 109 colony-forming units (cfu)/ml, or with a negative control (NC). Over a 5-day post-inoculation period, fecal scores, body weight, and growth performance were recorded. Thereafter, pigs were humanely euthanized, ileal contents and fecal F18 and LT gene abundances were quantified, and ileal tissue was assessed ex vivo for transepithelial resistance (TER), FITC-dextran permeability (FD4), and active glucose and glutamine transport. Jejunum, ileum, and colon were examined for histomorphology, F18 attachment (in situ hybridization), chloride secretion (cystic fibrosis transmembrane conductance regulator [CFTR] protein), and proliferation (Ki67). Ileal gene expression of epithelial proliferation, maturation, and differentiation markers was analyzed.ResultsETEC-challenged pigs had higher fecal scores than NC (p = 0.01), without differences in average daily feed intake or gain:feed (p > 0.10). Average daily gain tended to be lower in the 108 ETEC group compared to the NC (p = 0.07). In ETEC pigs, F18 and LT gene abundances were elevated (p < 0.001) and F18 attachment increased across all intestinal segments (p < 0.10), being greatest in the ileum (p < 0.001). CFTR protein abundance increased in all regions with ETEC challenge (p < 0.05), and Ki67 abundance tended to be lowest in the 109 group (p = 0.08). Notch expression tended to increase (p = 0.08) and Hes1 tended to decrease (p = 0.08) with ETEC challenge, suggesting altered epithelial renewal dynamics. Nutrient transport, TER, and FD4 flux were unaffected (p > 0.10).Discussion/ConclusionA 5-day F18 ETEC challenge induced ETEC attachment and diarrhea. These findings support a model where F18 ETEC epithelial attachment drives diarrhea through an enterotoxin-mediated, CFTR-dependent secretory mechanism rather than structural epithelial damage.